Atrial Fibrillation and Ischemic Stroke: A Clinical Review - Migdady, Ibrahim; Russman, Andrew; Buletko, Andrew B. (Seminars in Neurology, 2021)
Atrial fibrillation (AF) is an important risk factor for ischemic stroke resulting in a fivefold increased stroke risk and a twofold increased mortality. Our understanding of stroke mechanisms in AF has evolved since the concept of atrial cardiopathy was introduced as an underlying pathological change, with both AF and thromboembolism being common manifestations and outcomes. Despite the strong association with stroke, there is no evidence that screening for AF in asymptomatic patients improves clinical outcomes; however, there is strong evidence that patients with embolic stroke of undetermined source may require long-term monitoring to detect silent or paroxysmal AF. Stroke prevention in patients at risk, assessed by the CHA2DS2-VASc score, was traditionally achieved with warfarin; however, direct oral anticoagulants have solidified their role as safe and effective alternatives. Additionally, left atrial appendage exclusion has emerged as a viable option in patients intolerant of anticoagulation. When patients with AF have an acute stroke, the timing of initiation or resumption of anticoagulation for secondary stroke prevention has to be balanced against the risk of hemorrhagic conversion. Multiple randomized clinical trials are currently underway to determine the best timing for administration of anticoagulants following acute ischemic stroke.
Keywords: ischemic stroke; atrial fibrillation; thromboembolism; anticoagulation; left atrial appendage closure